Effect of Genetic Polymorphism of Bovine Growth Hormone Gene on Preweaning Growth Traits in a Thai Multibreed Beef Population - China Supakorn; Supamit Mekchay; Voravit Siripholvat; Panwadee Sopannarath; Skorn Koonawootrittriron; Sornthep Tumwasorn (Agriculture and Natural Resources, 2007)
Growth hormone (GH) gene was investigated as a candidate gene for birth weight (BW) and weaning weight (WW) in a population of multibreed beef cattle of three crossbreds. Beef cattle involved consisted of Charolais, Brahman and Thai local native with different breed fractions. Screening polymorphisms within bovine GH gene was performed by using a single strand conformation polymorphism (SSCP) method and the result was confirmed by a sequencing analysis. To identify polymorphic sites within the bovine GH gene, primers were designed revealing 6 PCR fragments (GH1 to GH6). Four single nucleotide polymorphisms (SNPs) were found in the bovine GH gene of this cattle population. Two SNPs were found within the GH1 and GH2 fragments at nucleotide position 303 and 218 bp. The other two SNPs were located at position 208 and 388 bp of the GH5 fragment. No polymorphisms were found in the GH3, GH4 and GH6 fragments, respectively. The genotypic frequencies of GH1 were found to be 5.40, 85.40 and 9.20 percents for A1A1 A1B1 and B1B1, respectively. The genotypic frequencies of GH2 were found to be 90.00, 8.46 and 1.54 percents for A2A2, A2B2 and A2C2, respectively. The GH5 were found to be 2.31, 30.77, 17.69, 13.85 and 35.38 percents for A5A5, A5B5, B5C5, B5D5 and C5D5 genotypes, respectively. Considering haplotype of four polymorphic sites, only 17 haplotypes were identified in this population. The 212 and 215 haplotypes were found at a high frequency. Effect of four SNPs in each region genotype regions of GH for BW and WW indicated that GH1 influenced both BW and WW. However, the GH5 influenced only for BW (P<0.01). Animals with B1B1 of GH1 had the highest BW and WW but animals with A1A1 had the lowest of both traits (P<0.05). Animals with C5D5 of GH5 had the highest BW but animals with A5A5 had lowest BW (P<0.05). Moreover, haplotype of four SNPs were analysed and the results showed the animals with 313 and 325 haplotypes obtained high BW and WW, respectively (P<0.05). However, animals with 111 and 234 haplotypes obtained low BW and WW, respectively (P<0.05). Therefore, the producers should select animals with B1B1 and C5D5 genotypes to obtain high BW and WW. Moreover, mating system should be considered because intra- and inter-genic polymorphic regions or haplotypes has an effect on BW and WW.